The changes, formation and public policy measures of mental health in Chinese youth - Wang, Yuanchao; Tan, Guifeng; Zhu, Tao (Frontiers in Psychology, 2025)
Confidence is an important indicator of individuals’ mental health. Taking confidence as an indicator, this paper uses CGSS2010-2021 data to analyze the latest situation, changing trend and formation mechanism of mental health in Chinese youth. The results show that firstly, Chinese young people have strong confidence in their future development in the new era, and their status expectations lean toward the upper and middle classes are dominant. Secondly, under the background of continuous economic growth and continuous improvement of objective status, youth confidence in development has not been significantly improved, but slightly decreased, resulting in a “paradox of confidence in development.” Thirdly, the composition effect (the changes in formation mechanism of status expectations) caused the above paradox. The positive influence of objective social status significantly reduced, and the positive influence of income gap disappears or turns negative. Youth confidence in development no longer depends on “who I am,” but more on the “macro environment.” Such changes offset the gains brought by economic growth and objective status improvement, leading to a fall rather than a rise in youth confidence in development.